Vasorelaxant effect of quercetin on cerebral basilar artery in vitro and the underlying mechanisms study. Issue 5 (4th May 2018) - Yuan, Tian-Yi; Niu, Zi-Ran; Chen, Di; Chen, Yu-Cai; Zhang, Hui-Fang; Fang, Lian-Hua; Du, Guan-Hua
Abstract: The aim of this study is to investigate the vasorelaxant effect of quercetin on cerebral basilar artery in vitro and provide a preliminary discussion concerning the underlying mechanisms. Using a DMT-isolated micro vessel system, quercetin was found to exhibit a vasodilatory effect on basilar arteries contracted by potassium chloride (KCl), endothelin-1 (ET-1), and 5-hydroxytryptamine (5-HT). The vasorelaxant effect of quercetin was partially attenuated when endothelium cells were removed. L-NAME, indomethacin, and ODQ treatment also decreased the potency of quercetin. In endothelium-denuded rings, the vasorelaxant effect of quercetin was not influenced by K + channel inhibitors. However, quercetin inhibited KCl induced extracellular calcium influx and ET-1 induced transient intracellular calcium release in a Ca 2+ -free solution. In conclusion, quercetin induced relaxation of the basilar artery in vitro is partially dependent on endothelium, which is mainly related to NO and COX pathways. It also induces relaxation through blockage of calcium channels. Abstract :